Determinants of tuberculosis among adult people living with HIV on antiretroviral therapy at public hospitals in Hawassa City, South Ethiopia - Asefa, Ahmed; Bolka, Habte; Woldesemayat, Endrias Markos (Frontiers in Epidemiology, 2024)
Background: The burden of TB/HIV co-infection is high in the sub-Saharan African countries. This study aimed to identify determinants of TB among peoples living with HIV (PLHIV) on antiretroviral therapy (ART) at public hospitals in Hawassa City Administration, Sidama Region, Ethiopia. Methods: A facility-based case the group without TB study was conducted from March 14–April 30, 2023. We employed a systematic random sampling to recruit participants. Cases were all adult people living with HIV (PLHIV) who developed TB after ART initiation, and the group without TB were all adult PLHIV who did not develop TB after their ART initiation. Data were collected from patients' medical records using Kobo-tool and then exported to SPSS Version 26 for analysis. A multivariable logistic regression was used to identify predictors of TB. Statistical significance was defined using the 95% confidence interval. Result: A total of 124 cases and 249 people without TB participated in the study. In a multivariable logistic regression analysis, we identified five independent determinants of TB. These include age (adjusted odds ratio (AOR)=2.7; 95% CI 1.4-5.2), patients’ residency (AOR= 6.4; 95% CI 2.8-14.5), WHO clinical stage III or IV (AOR=6.7; 95% CI 3.2-14.0), 3HP prophylaxis using (AOR=0.5; 95% CI 0.2-0.9), and having of other opportunistic infection (AOR=3.6; 95% CI 1.7-7.6). Conclusion and recommendation: A number of risk factors of TB were identified among PLHIV. Strengthening TB screening in advanced disease conditions, encouraging use of 3HP prophylaxis and early diagnosis and treatment of opportunistic infections were recommended to reduce the incidence of TB among PLHIV.